Digital technologies in the development of economic potential (Texas Journal of Multidisciplinary Studies, 2024)
The information society is a society in which the majority of people working in it are engaged in the production, storage, processing and sale of information, especially knowledge, which is its highest form. This stage of development of society and the economy is characterized by a further increase in the importance of information, knowledge and information technology in the life of society. As well as a comprehensive analysis of the development of the digital economy in both developing and developed countries, consideration of key trends, problems and opportunities. We analyzed how different the methods of developing the digital economy are from representatives of countries with developed and developing economies